The empirical evidence on the determinants of fiscal decentralization (2020)
This paper analyzes the main determinants of fiscal decentralization in a sample of eighty-four countries. The empirical findings show that the most consistent variable affecting fiscal decentralization is the size of a country: as land size increases, the level of fiscal decentralization increases as well. Countries with higher income equality, an educated population, more democratic, more urbanized and open to trade are also more likely to be more decentralized, though the findings demonstrate that there are regional and income variations. The most important policy implication is that governments interested in deepening the devolution of fiscal responsibilities to sub-national levels may consider acting to affect those variables that have been shown to exert a positive influence on this process.